A healthy, premoult adult king penguin (Aptenodytes patagonicus) with a markedly twisted beak. (9th November 2017) - Corbeau, Alexandre; Bost, Charles-André
Abstract : In seabirds, diet and feeding methods are related to the species morphology (Croxall, Evans, & Schreiber, 1984 ). Species that feed on living, mobile resources rely on a fully operational beak to efficiently seize, kill and swallow their prey. This is particularly important to diving species, such as penguins, that are highly time constrained when searching for prey at depth—as air-breathing predators, penguins must maximise their feeding efficiency during their deep foraging dives (Wilson & Wilson, 1990 ). This is why the observation of free-ranging penguins with physical abnormalities in good body condition is so rare. Here we report a highly unusual observation of a premoult adult king penguin ( Aptenodytes patagonicus Miller) in good body condition with a highly anomalous beak.